Introduction - Conflits environnementaux et gestions communautaires des aires naturelles protégées en Afrique francophone - Nicolas Hubert; Stéphanie Leyronas; Jessica Andriamasinoro; Alexis Nagalo (VertigO, 2025)
In most French-speaking countries of sub-Saharan Africa, environmental conservation areas are largely the legacy of colonial occupation. For more recent protected areas, their conceptualization, establishment and management programs are almost exclusively carried out by international players, in more or less close collaboration with national authorities, and with varying degrees of consultation and integration of local communities living in or near these environmental spaces. Presented as international development projects, these protected areas are for the most part created ex nihilo, and are only weakly integrated into the territories and their socio-environmental, political and economic structures. This introduction to the thematic issue provides a non-exhaustive synthesis of the literature on protected areas, environmental conflicts and the prospects for community integration and management by and for riparian communities. It examines how, on the one hand, the endogenous environmental, social and political norms and practices of riparian communities can contribute to the conservation of biodiversity and, on the other, how their integration into the management processes of natural protected areas can help strengthen environmental conservation programs and the appropriation of the environmental services they can provide.